Existence theory and numerical simulation of HIV-I cure model with new fractional derivative possessing a non-singular kernel - Aliyu, Aliyu Lsa; Alshomrani, Ali Saleh; Li, Yongjin; İnç, Mustafa; Baleanu, Dumitru (Springeropen, 2019)
In this research work, a mathematical model related to HIV-I cure infection therapy consisting of three populations is investigated from the fractional calculus viewpoint. Fractional version of the model under consideration has been proposed. The proposed model is examined by using the Atangana-Baleanu fractional operator in the Caputo sense (ABC). The theory of Picard-Lindelof has been employed to prove existence and uniqueness of the special solutions of the proposed fractional-order model. Further, it is also shown that the non-negative hyper-plane a positively invariant region for the underlying model. Finally, to analyze the results, some numerical simulations are carried out via a numerical technique recently devised for finding approximate solutions of fractional-order dynamical systems. Upon comparison of the numerical simulations, it has been demonstrated that the proposed fractional-order model is more accurate than its classical version. All the necessary computations have been performed using MATLAB R2018a with double precision arithmetic.
Keywords: Existence; Uniqueness; Positivity; Picard-Lindelof; Numerical simulation